Meaning-Making Processes in Adolescents After Experiencing Parental Divorce - Nikolova, Mariana; Chen, Daniel (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to explore the meaning-making processes of adolescents who have experienced parental divorce. Methods and Materials: A qualitative research design using a phenomenological approach was employed to capture adolescents’ lived experiences. The study included 24 adolescent participants aged 13 to 18 from various provinces in Canada who had experienced parental divorce within the past five years. Participants were recruited through purposive sampling, and data collection was conducted using semi-structured in-depth interviews. Thematic saturation was achieved by the 24th interview. Interviews were transcribed verbatim and analyzed using thematic analysis through NVivo software, allowing for the identification of recurring patterns and central themes. Findings: Analysis revealed four major themes: Emotional Navigation, Identity Reconstruction, Relational Shifts, and Meaning Construction. Adolescents initially experienced emotional confusion, sadness, and resentment, but some later developed emotional acceptance and resilience. They reported shifts in identity, including reevaluating family roles, trust, and future expectations. Relationships with parents, siblings, and peers were redefined, often marked by conflict, closeness, or detachment. Adolescents engaged in various cognitive strategies to make sense of the divorce, including narrative building, reframing, and philosophical reflection, which contributed to a renewed sense of self and outlook on future relationships. Conclusion: Adolescents are active agents in processing parental divorce, engaging in complex meaning-making that influences their emotional well-being and developmental trajectory. These findings underscore the need for therapeutic and educational interventions that center adolescents’ narratives and support reflective, adaptive meaning-making.